Asuhan Kebidanan Continuity of Care (COC) Ny. M G2P1A0 hamil 40 minggu di Tempat Praktek Mandiri Bidan: Midwifery Care Continuity of Care (CoC) Mrs. M G2P1A040 Weeks Pregnant at Independent Midwife Practice - Fitria, Fitria Endah Purwani; Ernawati; Rizka Kasilah (Journal of Holistics and Health Sciences, 2024)
Based on the regulation of the Minister of Health of the Republic of Indonesia 320 of 2020 concerning professional standars for midwives, the authority of midwives is maternal health services, child health services, and women’s reproducyive health services and family planning. The purpose of writing this article is to provide comprehensive care for Mrs”M” 26 years old G2P1A0 at TPMB Fitria Endah Purwani, SST.,M.Keb. research method: the research design used is descriptive and the type of research is case study. Guidelines for observation, interviews and documentation studies in the form of midwifery care (SOAP) format. Result: the di diagnosis obtained from the examination result was G2P1A0 39weeks pregnant in partu during the first active phase, live single fetus with head presentasion. Delivery time Mrs. the active phase “M" in the first stage lasts 5 hours, in the second stage 50 minutes, in the third stage 15 minutes, and in the fourth stage it lasts 2 hours without any complications. Midwives have carried out 60 steps of normal birth care (APN) and five common threads of care.   ABSTRAK Berdasarkan Peraturan Menteri Kesehatan Republik Indonesia 320 Tahun 2020 tentang Standar Profesi Bidan, kewenangan bidan yaitu pelayanan kesehatan ibu, pelayanan kesehatan anak, dan pelayanan kesehatan reproduksi perempuan dan keluarga berencana. Penulisan artikel ini adalah memberikan asuhan komprehensif pada Ny. “M” usia 26 tahun G2P1A0 di TPMB Fitria Endah Purwani, SST., M.Keb. Desain penelitian yang digunakan yaitu deskriptif dan jenis penelitian yaitu studi kasus. Pedoman observasi, wawancara dan studi dokumentasi dalam bentuk format Asuhan Kebidanan (SOAP). Diagnosa yang didapatkan dari hasil pemeriksaan yaitu G2P0A0 hamil 39 minggu inpartu kala I fase aktif, janin tunggal hidup presentasi kepala. Lama persalinan Ny. “M” kala I fase aktif berlangsung selama 5 jam, kala II 50 menit, kala III 15 menit, dan kala IV berlangsung selama 2 jam tanpa ada komplikasi. Bidan telah melakukan 60 langkah asuhan persalinan normal (APN) dan asuhan lima benang merah.